The Analysis of the Character of Tess of the D’Urbervilles - Yuan-yuan, Peng (Advances in Social Sciences Research Journal, 2018)
Tess is the outstanding realistic writer Thomas Hardy’s typical criticism of the old moral characters. Tess marks the birth of the new image of new agricultural workers, even though she is weak in the thoughts, but in front of the disaster of fortitude and dedication, sacrifice made her become a tragic character. In Hardy's eyes, Tess's all gifts were her greatest beauty, and she was a pure man. But she was tortured by all the tangible and invisible evils of society, and finally became a pathetic victim.